The Contribution of Sustainable Tourism to Economic Development: A Bibliometric Approach - Setiawati, Rahmi; Syaiful, Muhammad; Supriandi, Supriandi (West Science Interdisciplinary Studies, 2024)
This study employs bibliometric analysis to investigate the expansive field of sustainable tourism, focusing on the thematic evolution, research trends, emerging opportunities, and author collaboration networks from 1990 to 2024. Through a comprehensive review of the literature using VOSviewer, we identified key thematic clusters such as economic impacts, governance structures, social dimensions, and innovative practices in sustainable tourism. The temporal analysis revealed a shift in focus towards innovation and stakeholder perceptions, underscoring the dynamic nature of this research area. Emerging opportunities in the field include integrating advanced technologies and exploring the impact of local policies on sustainable tourism practices. Furthermore, the analysis of author collaboration networks highlighted the importance of scholarly partnerships in advancing the discourse, with prominent researchers playing pivotal roles in bridging various aspects of the field. This study not only maps the existing landscape but also highlights potential pathways for future research, aiming to enhance the efficacy and scope of sustainable tourism.